Youth in flames : a teenager's resistance and her fight for survival in the Warsaw Ghetto - Ṿiṭis-Shomron, ʻAlizah (2015)
"Aliza Vitis-Shomron was born in Warsaw into a wealthy merchant family, where Jewish tradition mixed with Polish culture. In September 1939, when the Nazis began their reign of terror in Europe and invaded Poland, Aliza was eleven years old. In her diaries–furtively written on scraps of precious paper that she kept throughout the war–she described the history of her family, struggling to survive in the occupied Warsaw Ghetto. Those diaries and later writings formed the basis for this memoir. Becoming a member of Hashomer Hatzair, the noted youth movement in the Warsaw Ghetto, gave Aliza hope and encouraged her to fight for survival